(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: Health workers need PPE when providing birth assistance to reduce the risk of contracting disease. There are health workers who have deficient behavior in implementing PPE. A preliminary study conducted from the results of questions and answers on 4 midwives in the Awayan Community Health Center working area showed that the 4 midwives had not used complete PPE. Non-compliance with midwives also has an impact on a midwife’s behavior in using PPE, the risk of a midwife being infected with blood borne diseases such as HIV infection, Hepatitis etc. from needle stick wounds is 61.34%. Objective: This study aims to analyze the attitudes and compliance of midwives in using PPE when providing midwifery services in the Awayan Community Health Center Work Area. Methods: This type of research is analytical observational research with a cross sectional research design conducted in February 2024 using chi-square analysis. This research involved 31 respondents in the Awayan Community Health Center UPTD working area. Results: Gloves were the most obediently used PPE (100%), while the fewest ones used face protection PPE (goggles) (22.5%). A total of 31 midwives who were negative about using PPE, all of them did not comply with using PPE (100%). Meanwhile, 8 midwives (25.8%) had a supportive attitude and complied with using PPE, although there were still 3 midwives who were positive but still disobedient in using PPE (9.7%). Based on the results of the Chi Square test, there is a significant relationship if the p-value is <0.05 and OR 8.000 for midwives who are negative for having a tendency to not comply with the use of PPE. Conclusion: The results of this study can be concluded that midwives’ negative attitudes towards using PPE risk increasing non-compliance with the use of PPE when providing midwifery services.